?Tu educaste tua mulher??: uma an?lise enunciativo-discursiva do discurso sobre a educa??o da mulher em Econ?mico de Xenofonte - Santos, J?ssica Maiana Ribeiro dos (2024)
The book VII of Xenophon's Economics presents the dialogue between Socrates and Ischomachus in the portico of the temple of Zeus Eleutherius regarding the education of a wife. The linguistic and enunciative characteristics of the dialogue are submitted in this work to the enunciative-discursive analysis proposed by Maingueneau, (2005, 2008, 2013, 2015), with the objective of examining how the enunciator's linguistic maneuvers constitute the interdiscourse, the discursive enactment and the discursive ?thos. The enunciative analyzes make explicit and show how the presuppositions of male authority and female obligation underlie the form of conversational interaction with a view to the apparent achievement of good administration of the home by the couple, theme of the Economic. The objective of this work is to demonstrate how the discourse analysis applied to the Xenofontean text shows that the emulation of a conversation in a public environment, marked by regularity and productivity of the spontaneity effect. This discourse aims to naturalize and hegemonize the perspective of citizen and landowner masculinity in relation to the feminine. Discourse and pragmatic analysis, in this work, allowed us to conclude that behind the teaching of educating the wife so that she was capable of managing the house, there was a conventional economic rhetoric in which marriage was conceived as an aspect of subordination to relationships and structures. civic, reinforcing educational pedagogy as a way of regulating and disciplining women as a figure contained in the home.